2002
DOI: 10.1034/j.1399-0004.2002.620210.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal muscular atrophy in black South Africans: concordance with the universal SMN1 genotype

Abstract: Only one study has reported on the genetic basis of spinal muscular atrophy (SMA) in South African subjects. This was conducted in the Johannesburg region and has suggested that black South Africans only (indigenous Africans) differ from the norm. We have explored this further by DNA studies in 30 unrelated and racially diverse patients who reside in the Western Cape, and who were assessed as SMA subjects according to the internationally accepted inclusion criteria for SMA. These subjects were seen at the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
9
1
Order By: Relevance
“…In this retrospective study, four of the patients recruited were suffering from SMA type 1, sixteen presented with SMA type 2, and ten were suffering from SMA type 3. Contrary to the earlier report [ 14 ], Wilmshurst and colleagues [ 15 ] reported 100% homozygous deletions of exon 7 or exons 7 and 8 of the SMN1 gene in all patients and concluded that the study subjects were not genetically or phenotypically different from internationally recognised forms of SMA. The differences in the outcomes of the two studies, though, could be due to the fact that the latter study excluded patients who showed facial musculature.…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…In this retrospective study, four of the patients recruited were suffering from SMA type 1, sixteen presented with SMA type 2, and ten were suffering from SMA type 3. Contrary to the earlier report [ 14 ], Wilmshurst and colleagues [ 15 ] reported 100% homozygous deletions of exon 7 or exons 7 and 8 of the SMN1 gene in all patients and concluded that the study subjects were not genetically or phenotypically different from internationally recognised forms of SMA. The differences in the outcomes of the two studies, though, could be due to the fact that the latter study excluded patients who showed facial musculature.…”
Section: Resultscontrasting
confidence: 73%
“…Wilmshurst et al [ 15 ] explored this further through genetic studies in thirty unrelated and racially diverse SMA patients (including 12 black patients) in the Western Cape area of South Africa. In this retrospective study, four of the patients recruited were suffering from SMA type 1, sixteen presented with SMA type 2, and ten were suffering from SMA type 3.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of small intragenic SMN1 mutations and/or of SMA unlinked to chromosome 5q13 may be higher in certain non-European populations, such as black South African patients [53], although data that do not support this hypothesis also exist [54].…”
Section: Smn1 Small Intragenic Mutationsmentioning
confidence: 94%
“…Within the last few years, there have been several reports on SMN and NAIP gene deletions in SMA patients of different ethnic origins: including French [3], Chinese [12], African [15], American [16] and many other groups. However, detailed information pertaining to the analysis of these genes in clinically diagnosed SMA patients from India is still lacking.…”
Section: Introductionmentioning
confidence: 99%